Investigation and optimization of parameters for hard turning of OHNS steel. Issue 10 (26th July 2020) - James Dhilip, Jafrey Daniel; Jeevan, J.; Arulkirubakaran, D.; Ramesh, M.
ABSTRACT: This work focusses on turning of hardened material which has rockwell hardness of C scale ranging from 45 to 70. Oil Hardened Non-Shrinking Die Steel (OHNS) finds its application in manufacturing of punches and cutters for milling due to its hardness and better machining. This work focuses on maximizing the material removal rate (MRR) and minimizing machining time and surface roughness. Turning was done using a carbide insert out using a computer numerical control machine. The experiments were done according to L'9 array and the output characteristics were analyzed. The percentage of contribution of input parameters when compared with output parameters were analyzed using analysis of variance. Grey relational analysis was used for optimizing the output characteristics. After optimisationa confirmation experiment was carried out for validation of results.